PENGAWASAN INTERNAL PENGELUARAN KAS PADA BAGIAN KEUANGAN SETDAKAB NAGAN RAYA - said mahdani (Universitas Teuku Umar, 2021)
Internal control has the responsibility for preparing the information about its adecuacy and effectifity of an organization internal control. There are several basic element of the internal control, becoming the issues that should be known namely: How the internal control for cash expenditure at financial department of Setdakab Nagan Raya? The Hipotesis in this research is the financial department of Setdakab Nagan Raya has enough its own cash expenditure internal control.The result of the research shown that the cash expenditure internal control that implemented at Financial Department of Setdakab Nagan Raya is effective enough eventhough there are some weakness. Badan Pengawasan Daerah (Bawasda) is controlling the process of APBD implementation by SKPD. So far, the running fuctions is the controlling of the activities based on the costumer payment request before the payment is paid. For the activity that is confirmed due to the payment request, it will be recommended for the financial department to pay the activity payment. However, the function of regular controlling is not effectively running yet for the limited of human resource available shown by regular financial auditing report for special purpose for several SKPD.Keyword: